2015
DOI: 10.1371/journal.pone.0119100
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Paraoxonase 1 Genetic Polymorphisms and Smoking and Their Effects on Oxidative Stress and Lung Cancer Risk in a Korean Population

Abstract: BackgroundFew studies in epidemiology have evaluated the effects of gene-environment interaction on oxidative stress, even though this interaction is an important etiologic factor in lung carcinogenesis. We investigated the effects of the genetic polymorphisms of paraoxonase 1 (PON1), smoking, and the interaction between the two on lung cancer risk and oxidative stress.MethodsThis study’s subjects consisted of 416 newly diagnosed lung cancer patients and an equal number of matched controls. The GoldenGate assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…The present study showed a higher 8-OHdG expression and secretion in airways of lung cancer patients than that of noncancer controls, which was agreed with previous findings in peripheral blood and urinary [ 21 – 23 ]. Interesting, the levels of 8-OHdG in BALF were associated with the TNM stage, which indicated that oxidative DNA damage was an indicator for the development of lung cancer.…”
Section: Discussionsupporting
confidence: 94%
“…The present study showed a higher 8-OHdG expression and secretion in airways of lung cancer patients than that of noncancer controls, which was agreed with previous findings in peripheral blood and urinary [ 21 – 23 ]. Interesting, the levels of 8-OHdG in BALF were associated with the TNM stage, which indicated that oxidative DNA damage was an indicator for the development of lung cancer.…”
Section: Discussionsupporting
confidence: 94%
“…43 Moreover, a strong linkage disequilibrium between the CYP3A4 rs2242480 and CYP3A5 rs776746 polymorphism was reported by several studies. 16,44 There are more and more studies considering genegene or gene-environment interaction in relationship with various diseases and drugs, such as breast cancer, 45 lung cancer, 35,46 warfarin, 47 and coumarins. [38][39][40] Unlike traditional pharmacogenetics analysis focused only on a single SNP, gene-gene and gene-environment interactions take genetic and environmental context into account, which is more powered in complex diseases and drug responses.…”
Section: Discussionmentioning
confidence: 99%
“…Only CYP1A2 was associated with the genetic polymorphisms present in gastric cancer. The effect of AFB 1 on gastric carcinogenesis may not be modulated by genetic polymorphisms of AFB 1 metabolic enzymes [111].…”
Section: Epigeneticsmentioning
confidence: 98%